THE ROLE OF OPEN MARKET OPERATIONS IN ENSURING BANKING SYSTEM STABILITY - Khudoyberdiyev Jonibek Sadriddin ugli, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The stability of the banking system is a key prerequisite for sustainable economic growth, effective monetary policy transmission and confidence in financial institutions. In modern central banking, open market operations are among the most important market-based instruments used to regulate banking sector liquidity, guide short-term interest rates and support the smooth functioning of payment and credit markets. This article examines the role of open market operations in ensuring banking system stability, with particular attention to the institutional context of Uzbekistan. The study analyzes repo and reverse repo operations, outright securities transactions, central bank bills, collateral mechanisms and the transmission of policy-rate decisions to the interbank money market.